A Social Support Theory of Desistance - Chouhy, Cecilia (Journal of developmental and life-course criminology, 2020)
Following Cullen’s spirit when setting forth his version of social support theory, this article shows the value of social support as an organizing concept for life-course theory. Specifically, this article describes four different pathways through which social support matters for desistance. First, social support is a constitutive part of adults’ social bonds that operate as resources that make change possible in individuals’ lives. Second, social support can promote and help sustain a cognitive transformation that encourages desistance. Third, socially supportive interventions are better equipped to promote desistance, whereas punishment-oriented interventions (those lacking and undermining social supports) are criminogenic. Finally, social support can help former inmates navigate the many stressors they encounter upon release and contribute to sustaining their desistance.